(untitled) (Biodiversitas Journal of Biological Diversity, 2015)
Afshar F, Sheidai M, Talebi SM, Keshavarzi M. 2015. Bayesian and Multivariate Analyses of combined molecular and morphological data in Linum austriacum (Linaceae) populations: Evidence for infraspecific taxonomic groups. Biodiversitas 16: 179-187. Plant specimens of Linum austriacum (Linaceae) were collected from 16 geographical populations of nine provinces in Iran and used for morphological and molecular (ISSR) analyses. Different multivariate and Bayesian methods were used to study interpopulations differences. Analysis of variance test and Principal coordinate analysis plots indicated morphological difference of the populations. Mantel test revealed positive significant correlation between morphological and geographical distance of these populations. Pearson, coefficient of correlation showed significant correlations between basal leaf length, width and length/width ratio with latitude and altitude of the studied populations. Bayesian analysis of combined molecular and morphological features revealed divergence of the studied populations and consensus tree showed separation of 6 populations in different clusters. Canonical Variate Analysis plot of these populations showed that Sang Sefid and Salmas populations differed greatly from the other populations. New ecotypes are suggested for these populations.